Ultrasensitive Photodetector: Edge‐State‐Enhanced Ultrahigh Photoresponsivity of Graphene Nanosheet‐Embedded Carbon Film/Silicon Heterojunction (Adv. Mater. Interfaces 11/2019). Issue 11 (7th June 2019) - Zhang, Xi; Lin, Zezhou; Peng, Da; Ye, Lei; Zang, Jianfeng; Diao, Dongfeng
Abstract : Graphene edge states have superior properties for photo‐electron trapping. In article number1802062 by Xi Zhang, Dongfeng Diao, and co‐workers, a van de Waals heterojuction is reported with an ultrahigh responsivity of 61.52A W −1 and a high specific detectivity of 3.04 × 10 14 Jones. Edge state modulates the Fermi‐level and reduces the recombination rate of photo‐excited electron‐hole pairs.